General English Online Teaching Within Pandemic Outbreak: Between Need and Satisfaction - Hamzani Wathoni; Hasan Basri; Astrid Dwimaulani; Dukha Yunitasari (Universitas Bengkulu, 2022)
Since the COVID-19 pandemic entered Indonesia in 2019, a technological adjustment in learning has been massively implemented. Online teaching is the only logical method for the reason of limiting physical contact. Although the characteristics of Z-Generation learners are digital natives, live learning is still more welcomed. Therefore, this study aims to determine and carefully measure the satisfaction of new colleges students in the general English program at Universitas Hamzanwadi. The measures are three aspects (course content, instructor performance, and media use) and another aspect in teaching mode (online and offline). In addition, this research discusses why the new college students choose to participate in the general English program 2020/2021. This study utilized a quantitative-descriptive approach with the census method. The population was taken from all new students for the 2020/2021 period as many as six faculties totaling 1450, although only 1196 respondents ultimately responded. The primary data collection instruments were questionnaires through google forms, interviews, and documents such as teaching modules and media. The findings show 1196 respondents recorded via a google form telling that the bilingualism reasons were the majority choice (54.93%). The scholarships and student exchanges are the second paramount concern to this program (21.15%). Other positions such as translator or work, reasons are not significantly mentioned. Conclusion tells that new student satisfaction following the General English program (GE) is significantly more than 70 percent in three aspects of the assessment within the program.